Heartbeats of a philosophy of writing: a conversation with Noé Jitrik - Giuliano , Facundo (2025)
This conversation explores a philosophy of writing based on the hesitation and creative energies that are knotted in the act of writing, assuming the implications of desire and the psychoanalytic impregnations that allow us to see the symptomatic, the entropic and the political that interweaves forgetfulness, sediments and fighting.